Transitioning from the Top Personal Continuity Planning for the Retiring Family Business Leader - Brun de Pontet, Stephanie (A Family Business Publication, 2018)
How can you move most effectively from the pinnacle of business and leadership success into "post-work" life that energizes you, and leverages your experience and your interests? This book draws on the experience of several past CEOs to address the important topic of 'personal continuity' for family business leaders transitioning from the day-to-day leadership of their enterprise. Making this transition remains challenging for most leaders. Lack of clarity or options for meaningful post-CEO roles is a major factor in succession struggles, resulting in wide-reaching consequences for all stakeholders in the enterprise. Here, family business consultant Brun de Pontet takes an in-depth look at the dynamics and challenges for leaders in transition and the systems around them, to deliver insights on sources of difficulty and tips and tools for effective planning. The book draws extensively on the experiences o f more than a dozen former family business leader interviewees. These highly driven and accomplished business leaders share stories and lessons from their own personal continuity journey as they transitioned from the top of their companies. Combining these real examples with knowledge from years of consulting and research, Brun de Pontet helps leaders broaden their sense of self as they look forward to a rich, purpose-filled next chapter in life.